Propriedades estruturais e eletrônicas de bicamadas de grafeno epitaxial e nanoestruturas do isolante topológico Bi2Se3 - Igor de Souza Lana Antoniazzi (2020)
Low dimensional materials, such as graphene, are highly susceptible to the substrate (interface) where they are supported. In this work, we investigate the properties of epitaxial graphene bilayers on oxidized silicon carbide (SiC). Graphene bilayers are obtained by O-intercalation between the epitaxial monolayer graphene and SiC. O-intercalation decouples the epitaxial graphene from the substrate by converting the buffer layer into a graphene layer and, simultaneously, oxidizes the SiC surface. After intercalation, the strain of epitaxial graphene is released and a high-quality AB-stacking bilayer graphene is formed. However, the oxidized interface degrades the electronic mobility of the bilayer graphene. In this work, several techniques were used to better understand the structure formed by O-intercalation and the origin of the low mobility observed in this type of material. The results show that at the interface there is a SiO2 rich layer and between it and SiC there is a transition layer formed by silicon oxycarbides (SiOxCy). Tunneling scanning spectroscopy (STS) measurements revealed that over the entire sample there is an intense density of states just around the Fermi level, which is responsible for suppressing the mobility of the charge carriers. According to theoretical calculations, these states are related to the formations of SiOxCy, present in the interface. Additionally, we propose a relatively simple and low-cost way for the production of heterostructures between topological insulators and graphene samples. We analyze the growth efficiency of Bi2Se3 topological insulators nanostructures on substrates of silicon oxide (SiO2/Si) and highly ordered pyrolytic graphite (HOPG). Preliminary results show the formation of reproducible triangular nanostructures on either substrate. The study of nanostructures through STS revealed that they present a low doping of charge carriers, which is related to the low density of Se vacancy, thus confirming the high quality of the structures.